Religion in The handmaid's tale : a brief guide - Tennant, Colette (Fortress Press, 2019)
From the significance of names to twisted uses of religion to the origins of the Ceremony, Religion in The Handmaid's Tale answers all of your questions about religion in Atwood's prophetic novel. For anyone who's ever googled a biblical precedent or religious phrase after encountering Atwood's dystopia, this essential guide explains it all and gives readers a fascinating look into the novel and its world. Read it and understand The Handmaid's Tale like never before.